ダイ 30 ジ ナンキョク チイキ カンソク タイ (1989-1990) ニ オケル PPB ジッケン ケッカ ノ イチ コウサツ - 門倉, 昭; カドクラ, アキラ; 江尻, 全機; エジリ, マサキ; 太田, 茂雄; オオタ, シゲル; 秋山, 弘光; アキヤマ, ヒロミツ; Kadokura, Akira; Ejiri, Masaki; Ohta, Shigeo; Akiyama, Hiromitsu (1991)
P(論文) 第30次南極地域観測隊では1990年1月に1機の極域周回気球(PPB)実験を行った。放球日は1月5日で, アルゴスシステムを利用して2月2日までの位置データ, 2月7日までのhouse keeping (HK)データを取得することが出来た。完全周回は実現出来なかったものの, 南極大陸の回りを約7/8周し, 気球工学上の様々な情報を得ることが出来た。高度を一定に保つためのオートバラスとシステムは正常に動作し, 放球後15日目にすべてのバラストを消費してしまうまで気球高度を27km以上に維持した。それ以後気球高度は次第に低下していった。15日目まで気球は西回りに約18.7°/日の安定した速さで周回していたが, 次第に周回速度が落ち, 1月25日には停滞し, 1月29日からは逆に東回りに動き始めた。気球高度での時々刻々の太陽天頂角と幾何学的日没時の太陽天頂角を計算し, バラスト投下量との関係を調べたところ, 1日のうちの太陽天頂角の最大値が92.4°より大きくなる頃からバラスト投下量が増大していることがわかった。また昭和基地上空の東西風の変化から気球の周回速度や周回方向の変化を説明することが出来た。 The 30th Japanese Antarctic Research Expedition (JARE-30) performed a Polar Patrol Balloon (PPB) experiment in January 1990. The launching date was January 5th. We could obtain position data until February 2nd and house keeping data until February 7th through ARGOS system. The trajectory of the PPB was about seven-eighth of a perfect circumpolar one. Auto-ballast system was normally operated to keep the flight level above 27km until 15 days after launch when all the ballast had been consumed, and then the balloon height became lower and lower. Before the ballast was completely consumed, the balloon drifted westward with a constant speed of about 18.7°per day by an easterly wind. After that the drifting speed gradually slowed down, eventually became zero on January 25th. On January 29th the balloon started drifting eastward. We calculated solar zenith angle and sunset angle at balloon height and found that the increase of ballast consumption began at the time when the maximum solar zenith angle became greater than a critical angle, in our case 92.4°. In order to understand the balloon drifting motion we referred to height profile data of zonal wind at Syowa Station during our flight. It was shown that when the balloon changed its drifting direction, the zonal wind direction was westerly at the balloon height. departmental bulletin paper